Predicting environmental problem-solving skills with a dynamic system in elementary education - Ilmi Zajuli Ichsan; Muzani Jalaludin; Bagus Sumargo; Ahmad Ali; Wiwin Pramita Arif; Dasmo Dasmo; Yusi Rahmaniar; Nurfadhilah Nurfadhilah; Maricar H. Sison; Ade Imas Rismayati (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2021)
Numerous environmental problems drive discussion to solve them. Students require environmental problem-solving skills to solve the existing problems. The study aimed to describe environmental problem-solving skills in Elementary Education. The research method is descriptive using a system dynamics approach. Instrument of Higher Order Thinking Skills (HOTS) and Pro-Environmental Behavior (PEB) used to measure students score in environmental topic. Sample was chosen by simple random sampling. The research used VENSIM software to create the modeling. The research results indicate that the score of the environmental problem-solving skills tends to increase due to the Higher Order Thinking Skills (HOTS) and Pro-Environmental Behavior (PEB). Moreover, there are other influencing factors including learning media and students’ activity in their environment. An increase of 5 points in the environmental problem-solving skills every year will be derived if the teachers perform various learning innovations. The research concludes that environmental problem-solving skills in low category and can be improve by various learning innovations.